The characteristic of pH sensing of potentiometric on zinc oxide and aluminium-doped zinc oxide nanostructures - Ain Zafirah Kamaruddin,; Lim, Kar Keng; Muhammad Azmi Abdul Hamid,; Al-Hardan, Naif H.; Huda Abdullah,; Al-Khalqi, Ensaf Mohammed (Penerbit Universiti Kebangsaan Malaysia, 2023)
Numerous investigations have been conducted to increase the sensitivity and stability of metal oxide semiconductors as pH-sensing membranes. This paper will describe the pH sensing and characterisation of zinc oxide (ZnO) and aluminium-doped zinc oxide (ZnO:Al) as potentiometric pH sensors. The hydrothermal technique was used to grow ZnO and ZnO:Al thin film nanostructures with doping concentrations of 1, 3, and 5 at% Al on the cleaned ITO substrates. The pH potentiometric sensing was performed in a wide pH range of 4-12 and produced sensitivity, including stability of the nanostructures. The prepared samples were also characterized by X-ray diffraction analysis (XRD), field effect scanning electron microscope (FESEM), and energy dispersive X-ray (EDX) to explore the influence of aluminium concentration on structural and morphology characteristics and then prepared as electrodes for pH sensing. From the XRD result, the sharp peaks and high peak intensities demonstrated well crystalline of the synthesized ZnO nanorods. Furthermore, the FESEM shows the growth of array nanorods perpendicular over the surface of ITO. The sensitivity of the pH sensor with 3 at% ZnO:Al exhibits higher sensitivity (43.80 mV/pH) and larger linearity (0.9507).